UPAYA ORANGTUA DALAM MENGENALKAN PENDIDIKAN SEKS PADA ANAK USIA DINI MELALUI TOILET TRAINING - Uswatun Hasanah; Much Deiniatur; Aguswan Khotibul Umam; Rezki Febriana (Institut Agama Islam Negeri Metro, 2020)
Sex education must be started from the family, especially the role of the two parents who must introduce sex education. One way of introducing sex education to early childhood is through toilet training. Toilet training of children is an effort to train children to be able to control their urination and defecation. The purpose of this study was to determine the role of parents in introducing sex education to children through toilet training. The research used qualitative approach (field research) which was conducted at Perum Palm Asri Sumber Cirebon. Data collection techniques in this study were observation, interviews, and documentation. The finding of the research is the sex education is very important to be introduced to children from an early age, especially with regard to the introduction of reproductive organs and sex. The strategy of parents by explaining to children that the reproductive organ in the front is testis for peeing. While the back (rectum) for defecation. Keywords: Sex Education, Toilet Training, Early Childhood